Crystallization of Piroxicam Solid Forms and the Effects of Additives. Issue 8 (9th July 2014) - Liu, Guangpu; Hansen, Thomas B.; Qu, Haiyan; Yang, Mingshi; Pajander, Jari P.; Rantanen, Jukka; Christensen, Lars P.; Qu, Haiyan; Rantanen, Jukka; Ulrich, Joachim
Abstract The relative stabilities of the two anhydrous polymorphs and the monohydrate of piroxicam in ethanol/water mixtures and the crystallization behavior of the solid forms in the presence of 11 additives were studied. At 37 °C, form II is thermodynamically more stable than form I, while the relative stability of form II and the monohydrate depends on the water concentration in the solution. The total Hansen solubility parameter δT and the hydrogen bonding solubility parameter δH of the substances can partly explain the effects of the additives on the crystallization of the solid forms. The additives that selectively promoted the crystallization of form I are the ones with δT and δH parameters similar to those of piroxicam.